Miliary opacities in pulmonary sarcoidosis. Issue 5 (18th April 2020) - Sugino, Keishi; Ono, Hirotaka; Ando, Masahiro; Igarashi, Seiji; Kurosaki, Atsuko; Tsuboi, Eiyasu
Key message: Pulmonary sarcoidosis should be considered in the differential diagnosis of miliary opacities in bilateral upper lobes predominance. Abstract : We present a rare case of a 37‐year‐old woman diagnosed with pulmonary sarcoidosis who presented with unusual bilateral upper lobes miliary opacities on chest high‐resolution computed tomography.